CAREER GUIDANCE for INDIVIDUALS with ASPERGER'S SYNDROME (Autism Spectrum Disorder). - Bissonnette, Barbara (Career Planning & Adult Development Journal)
In the right job, with the right support, individuals with Asperger's Syndrome and similar autism spectrum profiles have much to offer employers. However, placing too much emphasis on interests can lead these students and clients to unsuitable jobs or careers. This article, interspersed with examples, explains how Asperger's impacts adults in the workplace, and why career professionals must use caution when applying standard assessments and protocols to this population.